A quaternary record of explosive eruptions along the Western Sunda volcanic arc: insights into the eruptive histories of volcanoes in Sumatra, Indonesia - Phua, Marcus (Nanyang Technological University, 2023)
Sumatra is a highly populated region in the vast Indonesian archipelago with at least 113 volcanic centres of varying morphologies distributed across the island that have or are likely to have produced eruptions in the geological past. Despite a likely frequent and explosive eruptive history, little is known about the characteristics and behaviours of these volcanic centres. This thesis draws on the complementary and distinctive features of tephra fall deposits predominantly preserved within the deep-sea environment and utilises the combined approaches of tephrostratigraphy and tephrochronology with the aim of improving our understanding of past explosive Sumatran eruptions. It also seeks to address specific knowledge gaps with respect to the moderately explosive (VEI 3-5) and highly explosive (VEI 6-8) eruptions in the region. In this thesis, a 74,000-year record of explosive eruptions (post-Youngest Toba Tuff eruption) throughout the Sumatran region was first established using a combination of proximal (onshore) and distal (offshore) eruptives, with a particular focus on the moderately explosive eruptions in terms of their geochemical characteristics, eruption ages, volumes, and magnitudes. This was then followed by an expansion of the limited record of highly explosive eruptions that occurred during the Quaternary period (pre-Youngest Toba Tuff eruption) with respect to their geochemical characteristics and eruption ages. This disparate, but methodical approach taken for the thesis provides insights into the variability of eruptive frequency (or recurrence rate of volcanic activity) of explosive eruptions throughout the Quaternary period (or the last ~2.58 Ma) and makes important contributions that promote and facilitate tephrostratigraphic, tephrochronological, and volcanic hazard assessment studies in the Sumatran region.